The historical value of Sheikh Maarouf Nodhi handwritings - صاڵح ئاراس محەمەد (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
Al-Shaikh al-Nudhi lived eighty-eight year, spending eighty years in achievement, teaching and education. He was a scientist in sciences and emam in classification and categorization and his talents benefit life’s alive and dead. The Sheikh is known for the handwritings messages, and he sent them to scientists and scholars in his time, and in these messages referring to some of the facts and historical signals. Analyze and analyze and derogate a number of such messages and analyze them to show aside from the political, scientific and social situation in those days.